A rare case of neonatal parotid abscess - Singh, Jatinder; Singh, Jaskaran; Bhardwar, Vaneeta; Kaur, Manmeet (International Journal of Contemporary Pediatrics, 2020)
Acute suppurative parotitis is not common in children and is exceptionally uncommon in neonates. Most common microorganism isolated is Staphylococcus aureus. We present a 22-day old, full-term, breast-fed, male neonate with a left-sided parotid abscess. The infant displayed a preauricular swelling, pain and redness. Pus discharged from cleared out Stensen’s channel on compression of the gland remotely. Early determination and intravenous anti-microbials are the keys to the treatment.